ARTHERY (Action and Rehabilitation to be Healthy for Geriatry) - Pratama, Rovy; Bulqiah, Mikyal (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
ARTHERY (Action & Rehabilitation to be heatlhy for Geriatry) is a social programs that have a long-term goal to improve the quality of life of the elderly who suffer knee osteoarthritis and prevents osteoartristis progression. The program is implemented at the UPTD Rumoh Seujahtra Geunaseh Sayang that is the only nursing home in the city of Banda Aceh for three months. The method applied in this program is introduce laterally wedged insoles and do osteoarthritis exercise. The results of the implementation of this program are improvement average of WOMAC scores on pain and stiffness of knee osteoarthritis in 13 people and 55 other elderly people have undergone knee osteoarthritis prevention program with 12 times oateoartritis exercise and wearing laterally wedged insoles.Keywords: Laterally wedged insoles, Osteoarthritis Exercise, UPTD Rumoh Seujahtra Geunaseh Sayang